Collagen interactions: Drug design and delivery - An, Bo; Lin, Yu-Shan; Brodsky, Barbara (Advanced drug delivery reviews, 2016)
Collagen is a major component in a wide range of drug delivery systems and biomaterial applications. Its basic physical and structural properties, together with its low immunogenicity and natural turnover, are keys to its biocompatibility and effectiveness. In addition to its material properties, the collagen triple-helix interacts with a large number of molecules that trigger biological events. Collagen interactions with cell surface receptors regulate many cellular processes, while interactions with other ECM components are critical for matrix structure and remodeling. Collagen also interacts with enzymes involved in its biosynthesis and degradation, including matrix metalloproteinases. Over the past decade, much information has been gained about the nature and specificity of collagen interactions with its partners. These studies have defined collagen sequences responsible for binding and the high-resolution structures of triple-helical peptides bound to its natural binding partners. Strategies to target collagen interactions are already being developed, including the use of monoclonal antibodies to interfere with collagen fibril formation and the use of triple-helical peptides to direct liposomes to melanoma cells. The molecular information about collagen interactions will further serve as a foundation for computational studies to design small molecules that can interfere with specific interactions or target tumor cells. Intelligent control of collagen biological interactions within a material context will expand the effectiveness of collagen-based drug delivery. [Display omitted]